REVIEW: AN ANALYSIS OF MONKEYPOX DISEASE AND CURRENT SCENARIO IN MALAYSIA - Mustaffa, Fazlina; Zaini, Nur Adilla; Selvarajah, Komathi (International Journal of Research -GRANTHAALAYAH, 2019)
Recently, there is large outbreak of monkeypox virus in Central Africa and this remains as a growing public health threat. The last confirmed case of monkeypox was in 1978 at Nigeria. Monkeypox is now a major threat to global health security, requiring an urgent multidisciplinary approach including virologists, veterinarians, physicians, and public health experts to fast‐track the development of diagnostic assays, vaccines, antivirals, and other control strategies. This aim of this manuscript is to provide information on the current state of knowledge about human monkeypox, with emphasis on epidemiologic characteristics, clinical features, diagnosis, treatment, and prevention.